Pengaruh Kondisi Fasilitas Sekolah terhadap Konsentrasi dan Kualitas Belajar: Studi pada Siswa SMPN 2 Sakra - Abdul Latif; Baiq Nurlita Handayani; Dini Damayanti; Lia Saputri; Zubaedah Zubaedah (Alpatih Harapan Semesta, 2026)
This study aimed to investigate the impact of school facility availability and damage on student concentration and learning quality at SMPN 2 Sakra. A quantitative descriptive-correlational approach was employed, involving a survey of 80 students and observations of school facilities. Data were analyzed using correlation and regression analysis. Statistical analysis indicated that higher availability of adequate facilities significantly improves students’ concentration and learning quality, whereas the presence of damaged or inadequate facilities negatively affects these outcomes. The results suggest that maintaining and improving school facilities is crucial for optimizing students’ academic experience. It is recommended that school administrators prioritize facility maintenance and resource allocation to enhance learning conditions. These findings contribute to understanding the role of the physical environment in education.